2021
DOI: 10.1111/sms.14086
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of high‐intensity exercise on the metabolomics profile of human skeletal muscle tissue

Abstract: The study aimed to identify and quantify the metabolites profile and metabolic pathways in human muscle tissue engaged during exhaustive high‐intensity cycling exercise. Seven healthy physically active men performed a graded exercise test and an exhaustive supramaximal effort at 115% of maximal aerobic power with muscles biopsies performed in rest and immediately after exhaustion for quantifying of muscle metabolites changes by 1H‐NMR spectroscopy. The time until exhaustion (tlim) recorded was 224.7 ± 35.5 s w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Contrary to the theory that above 80% of V’O 2 max, the contribution of fat oxidation is near negligible, 45 , 67 recent studies have shown that during HIIT, fat oxidation rates increase (i.e., threefold higher in well-trained athletes than in moderately active people), 18 as confirmed by metabolomics analysis. 68 In fact, fat oxidation during HIIT, compared to continuous exercise, occurred mainly due to increased levels of fatty acid transport proteins taking up plasmatic free fatty acids 69 in type II fibres of human skeletal muscle. 70 On the other hand, in COMB training, increased fat oxidation during MICT 34 primarily occurs in type I fibres 71 that exhibit high rates of intramuscular fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the theory that above 80% of V’O 2 max, the contribution of fat oxidation is near negligible, 45 , 67 recent studies have shown that during HIIT, fat oxidation rates increase (i.e., threefold higher in well-trained athletes than in moderately active people), 18 as confirmed by metabolomics analysis. 68 In fact, fat oxidation during HIIT, compared to continuous exercise, occurred mainly due to increased levels of fatty acid transport proteins taking up plasmatic free fatty acids 69 in type II fibres of human skeletal muscle. 70 On the other hand, in COMB training, increased fat oxidation during MICT 34 primarily occurs in type I fibres 71 that exhibit high rates of intramuscular fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to each constant‐load supramaximal trial, the participants remained at rest seated in a chair for 10 min in order to determine the resting values of V̇O 2 (assuming the V̇O 2 average of the last 2 min of rest) and the [La − ]. After a warm up (abovementioned), the individuals performed the constant‐load supramaximal effort at 115% of vV̇O 2max until the task failure, which was assumed as the incapacity to keep the running intensity (Zagatto, Bertuzzi, et al, 2016; Zagatto, Leite, et al, 2016; Zagatto, Miyagi, et al, 2017; Zagatto, Nakamura, et al, 2017; Zagatto et al, 2022). The TTE was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The oxygen equivalent from glycolytic energy pathway ( E [La − ] ) was estimated by net lactate concentration accumulation (i.e., difference between peak [La − ] and the baseline [La − ]; ∆[La − ]), assuming an oxygen equivalent 3.0 ml·kg −1 for each ∆[La − ] of 1 mmol·L −1 (Brisola et al, 2015; Di Prampero & Ferretti, 1999; Miyagi et al, 2017; Zagatto, Bertuzzi, et al, 2016; Zagatto, Leite, et al, 2016; Zagatto, Miyagi, et al, 2017; Zagatto, Nakamura, et al, 2017; Zagatto et al, 2022). Therefore, the anaerobic capacity was assumed as the sum of E PCr and E [La − ] (Brisola et al, 2015; Milioni et al, 2016, 2017; Miyagi et al, 2017; Zagatto & Gobatto, 2012; Zagatto, Bertuzzi, et al, 2016; Zagatto, Leite, et al, 2016; Zagatto, Miyagi, et al, 2017; Zagatto, Nakamura, et al, 2017; Zagatto et al, 2022). The oxygen equivalent from oxidative metabolism ( E OXID ) also was estimated considering the V̇O 2 area under the curve by trapezoidal method (Brisola et al, 2015; Milioni et al, 2017; Miyagi et al, 2017; Zagatto, Bertuzzi, et al, 2016; Zagatto, Leite, et al, 2016; Zagatto, Miyagi, et al, 2017; Zagatto, Nakamura, et al, 2017; Zagatto et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations